2002
DOI: 10.1071/ar01129
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar identification in upland cotton using RAPD markers

Abstract: Using the random amplified polymorphic DNA (RAPD) method, the identification and the genetic description of 28 upland cotton (Gossypium hirsutum L.) cultivars currently cultivated in Greece was attempted. Based on the results of a preliminary experiment using 50 ten-base arbitrary primers, 24 were selected for the main experiment. DNA bands totaling 181 were observed, 118 (65.2%) of which were polymorphic. On the average, 7.5 DNA bands were amplified per primer, 4.9 of which were polymorphic. The unique identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…These COP values from Bowman et al (1997) ranged from 0 to 0.75, their median being 0.051 due to skewness toward low COP values. The RFLP‐GS values had a normal‐shaped distribution, ranging from 0.914 to 1 with a median of 0.975, which reflects the low genetic diversity reported by Brubaker and Wendel (1994) and the narrow ranges of genetic distance and similarity reported by Pillay and Myers (1999), Iqbal et al (2001), Linos et al (2002), and Gutiérrez et al (2002) The distributions of COP and RFLP‐GS values were similar to those observed by Barrett et al (1998) in wheat using AFLP markers.…”
Section: Resultssupporting
confidence: 53%
“…These COP values from Bowman et al (1997) ranged from 0 to 0.75, their median being 0.051 due to skewness toward low COP values. The RFLP‐GS values had a normal‐shaped distribution, ranging from 0.914 to 1 with a median of 0.975, which reflects the low genetic diversity reported by Brubaker and Wendel (1994) and the narrow ranges of genetic distance and similarity reported by Pillay and Myers (1999), Iqbal et al (2001), Linos et al (2002), and Gutiérrez et al (2002) The distributions of COP and RFLP‐GS values were similar to those observed by Barrett et al (1998) in wheat using AFLP markers.…”
Section: Resultssupporting
confidence: 53%
“…The results in rice from this study suggest that RAPD-PCR was able to identify genetic differences between more distantly related rice cultivars [5], and this has also been reported for other plants [27,28]. These results must be considered and evaluated with some caution since the nature of the RAPD-PCR method means that normally it over estimates genetic differences.…”
Section: Rapd-pcr Screeningsupporting
confidence: 63%
“…Nature of genetic material could be responsible for different reports on the degree of perceived variations in cotton [1] [2]. Linos et al [3] reported that variations in the DNA sequences are identified by molecular markers which cannot detect the changes in the products of transcribed genes like biochemical and morphological markers. Moreover, several cultivars in a species showed a range of agroclimatic conditions required for the production and growth of cotton.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics should be genetically stable within the cultivars so they will reappear when the cultivars is grown again [3] [4]. Performance differences among cultivars are usually more difficult to identify than morphological features because they are more likely to be affected by the environment or more complex inheritance.…”
Section: Introductionmentioning
confidence: 99%